Relevance of Librarianship to the Society - Adedeji , Francis Adegboyega; Ahmed , Yakub Olayinka (MiddleBelt Journal of Library and Information Science, 2015)
The paper basically examines the relevance of librarianship in the society, and it also looked into the evolution of librarianship. The paper dwelled on the society and the need for libraries in the society. Emphases were also made on the role of the libraries to promote knowledge. Historical research method was adopted for the study. The challenges of librarianship were alighted and solution to the identified problems was made.